Babymouse. 20, Babymouse goes for the gold - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2016)
"Babymouse has big dreams ... and wet whiskers. She has joined the swim team and is ready to dive in. Next stop, the Olympics! But competitive sports aren't really her strong suit. Will hard work and determination earn her a gold medal?"--Amazon.com.
2.4
3-6.
3-6
Keywords: Animals -- Comic books, strips, etc -- Juvenile fiction; Babymouse (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Swimming -- Comic books, strips, etc -- Juvenile fiction; Animals -- Fiction; Babymouse (Fictitious character) -- Fiction; Mice -- Fiction; Swimming -- Fiction; Animals -- Comic books, strips, etc -- Fiction; Babymouse (Fictional character) -- Comic books, strips, etc -- Fiction; Mice -- Comic books, strips, etc -- Fiction; Swimming -- Comic books, strips, etc -- Fiction; Graphic novels; Humorous comics